ANALISIS KELAYAKAN USAHA TAMARILLO YOGURT DI INSTITUT BIO SCIENTIA INTERNATIONAL INDONESIA - Saraswati, Reni Mutiarani (Jurnal Riset Entrepreneurship, 2019)
Tamarillo Yogurt is a healthy drink developed by a group of students at the Institut Bio Scientia Internasional Indonesia. After several months of sales trial, the product has received a very good response from customers as well as good sales performance. Based on this, the founder aims to continue expanding their business even though the feasibility of the business is unknown yet. This research aims to analyze the business feasibility of Tamarillo Yogurt product. There will be two aspects of analysis, first is non-financial aspects such as market and marketing, management and organizational, technical, legal, socio-economic and environmental. The second is financial aspects that will use criteria such as NPV, IRR, Benefit/Cost Ratio and Payback Periods. In addition, the research will analyze whether the business is affected by the changes in cost and benefit of producing the products. The data used in the research will be based on primary data and secondary data. Based on financial and non-financial aspects, the result of the study shows that the business is feasible and profitable.